Species Diversity of Understorey Vegetation in Pinewood (Pinus merkusii) Forest in RPH Sempor, BKPH North Gombong - Ramadhan, Anang Yanuar; Sudiana, Eming; Widodo, Pudji (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2023)
Understorey plant is a type of basic vegetation under forest stands except for saplings. Understorey vegetation includes grasses, herbs, shrubs, and ferns. The presence of understorey vegetation can be used as an indicator of forest conditions and is expected to reduce disturbances to the forest. The purpose of this research is to determine the diversity and the dominance of understorey species under the pinewood stands based on pine ages in RPH Sempor, BKPH North Gombong. This research was conducted using a survey method and systematic sampling techniques at two different age groups pinewood forest of RPH Sempor, BKPH North Gombong. The result showed that the total understorey species found were 34 species from 21 families. The understorey species number found at the 25 years of pine forest was 22 species found and at the 45 years, there were 17 species. Based on the research that has been done, it can be concluded that the younger the age of pine stand, the more understorey species number. Evenness of the understorey species at two different ages of pine stand in RPH Sempor is evenly distributed, so there are no dominant species. The physicochemical factors measurement result showed that the canopy cover affected the temperature and humidity level, thus affecting the number of understorey individuals and the species number in each stand.